THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE: A CASE STUDY AT PT. MERPATI ALAM SEMESTA KARGO JAKARTA - Rahmayani, Rahmayani; Oktaviani, Silvia Rizki (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to analyze the effect of work motivation and work environment on employee performance of PT Merpati Alam Semesta Kargo Jakarta. Data were obtained through questionnaires from 53 operational employees with saturated sample technique, and processed using IBM SPSS Statistics 27.0. The results show that all indicators are valid and reliable. The classical assumption test shows that the data is normally distributed without symptoms of multicollinearity or heteroscedasticity. Hypothesis testing shows that work motivation has a positive and significant effect on performance (significance = 0.000 < 0.05), while the work environment has no significant effect (significance = 0.074 > 0.05). The F test shows that both variables simultaneously affect employee performance. The coefficient of determination (R²) shows that work motivation and work environment explain 64.5% of the variation in performance, while 35.5% is influenced by other factors not analyzed.